(untitled) (Journal of Intellectual Property Rights (JIPR), 2025)
Climate change mitigation and adaptation require the intervention of climate engineering methods that remit climate change. One such engineering method involves geoengineering technologies, which can be defined as technologies that seek to modify the already existing natural climatic conditions. Geoengineering or climate engineering is a mechanism that has been developed to curtail the negative effects on the environment, it is a method operating with the use of scientific modifications and formulae that can be considered as environmental innovation ambitiously working to negate the climate change problems. Environmental innovations play a key role in climate change mitigation, and the development and diffusion of climate innovations or environmental innovations have a deliberate positive effect on the climate. Geoengineering is a scientific modification or manipulation of the natural environmental systems that provides a possible solution to slow down and mitigate the effects of climate change. Intellectual property plays a substantial role in the research, development, and diffusion of geoengineering technologies. Patents for environmental inventions, such as geoengineering technologies, can be incremental in tackling the effects of climate change because they are new-age technologies promising to overcome the negative effects of climate change in the atmosphere.